Proteomics analysis of human mesenchymal stromal/stem cell sarcomagenesis model identifies ALDH1A3 and CD99 as potential targets in the transformation process - Gobin, Jonathan M.; Gao, Jun; Rey, Veronica; Tornín, Juan; Muradia, Gauri; Halabi, Hala; Bueno, Clara; Guerrero-Murillo, Mercedes; Lopez-Millan, Belen; Menendez, Pablo; Rosu-Myles, Michael; Rodriguez, Rene; et al. (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background Mesenchymal stromal/stem cells (MSC) may represent the cell-of-origin for sarcoma development. A collection of human MSCs sequentially mutated with an increasing number of oncogenic hits served to recreate a step-wise process of sarcomagenesis. To identify potential protein targets of interest in the MSC-sarcoma transformation process, quantitative mass spectrometry-based (LC–MS/MS) proteomics was performed. Results Among the protein hits identified as significantly regulated in the transformation process, ALDH1A3 and CD99 were selected and further studied. Both ALDH1A3 abundance levels and activity were significantly upregulated in early-phase (immortalized) and fully transformed (sarcoma forming) cells as compared to normal MSCs. Inversely, CD99 total protein and cell-surface abundance levels were downregulated in immortalized and transformed MSCs. Downregulated CD99 was also identified in several human bone and soft tissue sarcoma subtypes. Conclusions Proteomics investigation of a MSC-transformation model of sarcoma has yielded ALDH1A3 and CD99 as potential targets for sarcomagenesis that may contribute to a greater understanding of the disease and the development of novel therapeutic approaches.